2014
DOI: 10.1038/nri3701
|View full text |Cite
|
Sign up to set email alerts
|

Integrating canonical and metabolic signalling programmes in the regulation of T cell responses

Abstract: Over the past decade, our understanding of T cell activation, differentiation and function has markedly expanded, providing a greater appreciation of the signals and pathways that regulate these processes. It has become clear that evolutionarily conserved pathways that regulate stress responses, metabolism, autophagy and survival have crucial and specific roles in regulating T cell responses. Recent studies suggest that the metabolic pathways involving MYC, hypoxia-inducible factor 1α (HIF1α), AMP-activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
341
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(348 citation statements)
references
References 125 publications
(130 reference statements)
3
341
0
4
Order By: Relevance
“…In contrast, CD8 + memory T cells, which are programmed for long-term survival, have fewer acute metabolic needs and use oxidative phosphorylation rather than glycolysis (5,6). While recent work has indicated the importance of metabolic programming in T cell fate, the pathways that regulate T cell metabolism are still being elucidated (7). mTOR is an evolutionarily conserved serine/threonine protein kinase important for the integration of environmental cues to regulate cellular metabolism, protein synthesis, differentiation, survival, and growth (8).…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CD8 + memory T cells, which are programmed for long-term survival, have fewer acute metabolic needs and use oxidative phosphorylation rather than glycolysis (5,6). While recent work has indicated the importance of metabolic programming in T cell fate, the pathways that regulate T cell metabolism are still being elucidated (7). mTOR is an evolutionarily conserved serine/threonine protein kinase important for the integration of environmental cues to regulate cellular metabolism, protein synthesis, differentiation, survival, and growth (8).…”
Section: Cd8mentioning
confidence: 99%
“…We propose that TSC2 controls glycolysis in part by its ability to inhibit mTORC1 (7,46 In vitro stimulation of splenocytes was performed with soluble anti-CD3 (1 μg/ml) for 48 hours, followed by a 10-fold media expansion with IL-2 (1 ng/ml) or IL-7 (10 ng/ml) and IL-15 (20 ng/ml) for 3 to 5 days. Live cells were collected by density gradient separation (Ficoll, GE Healthcare) and then restimulated with plate-bound anti-CD3 (1 μg/ml) and soluble anti-CD28 (2 μg/ml) in the presence of GolgiPlug (BD Biosciences) overnight.…”
Section: Indeed T-tsc2mentioning
confidence: 99%
“…This metabolic reprogramming occurs in a Warburg-like fashion, independently of oxygen levels (22,72). The shift is primarily orchestrated by an mTOR-dependent nutrient-sensing pathway (73). The inhibition of glycolysis by 2-DG abrogates Th17 development (72).…”
Section: Hif1α and The Th17/treg Balancementioning
confidence: 99%
“…4,5 During this metabolic adaptation, AMPK (as AMPKa1, the predominantly-expressed isoform in T cells 33 ) has been shown to play an important role by regulating the activity of mTOR and the homeostasis of ROS. 34,35 In this regard, we found that AMPK activation (as marked by its Thr-172 phosphorylation) was stronger in both na€ ıve and activated PP4-deficient T cells (Fig. 6A).…”
Section: Ampk Hyper-activation Induced By Pp4 Deficiency May Contribumentioning
confidence: 72%
“…We believe that this discrepancy may be explained by the differential requirements of AMPK in tumor cells and activated primary T cells. 34,35 While tumor cells often constitutively turn on AMPK to adapt aerobic glycolysis for optimal expansion, primary T cells only transiently turn on AMPK following TCR activation. 33 The hyper-activation of AMPK may thus have different effects in tumor cells and activated T cells, so that the same G1-S block can be mediated via distinct pathways.…”
Section: Discussionmentioning
confidence: 99%